An Analysis of the Spatial Characteristics and Transport Fluxes of BTEX in Soil and Atmospheric Phases at a Decommissioned Steel Mill Site in China with a Long History - Xuwei Li; Wenyi Xie; Da Ding; Mengjie Wang; Lingya Kong; Dengdeng Jiang; Shaopo Deng (Toxics, 2023)
BTEX (benzene, toluene, ethylbenzene, and xylene), as characteristic pollutants in chemical plant sites, are widely present in the environment and pose a serious threat to the health and safety of nearby residents. Studying the spatial distribution characteristics and transport fluxes of BTEX in soil and air at contaminated sites and the health risks they pose to humans is of great significance for fine pollution control and environmental management. This study took a typical decommissioned steel plant as a case study. A total of 23 soil and air samples were collected from different locations to investigate the spatial distribution characteristics of BTEX in soil and air. The transport and fate of BTEX in soil and air were evaluated using the fugacity model, and finally, a human health risk assessment was conducted. The results indicate a relatively severe level of benzene pollution in both soil and air. The maximum exceedance factor of benzene in soil samples is 31.5, with the concentration exceedance depth at 1.5 m. The maximum concentration of benzene in air samples is 4.98 μg·m−3. Benzene, at 5.9% of the site, shows a low flux with negative values, while other components at various locations all exhibit a trend of transport from the soil phase to the atmospheric phase. Benzene is the pollutant that contributes the most to the transport flux from soil to air within the site. The coking area and sewage treatment area are key areas within the steel mill where BTEX accumulate easily in the soil. The non-carcinogenic risk values of the individual components of BTEX in the soil are below the acceptable risk level. However, the carcinogenic risk value of benzene in the children’s exposure scenario exceeds the carcinogenic risk level of 10−6. The carcinogenic risk range of various components of BTEX in the air is 2.63 × 10−6~3.88 × 10−5, with 28.6% of the locations exceeding the threshold of 10−6. The range of the total HI (hazard index) is 2.08 × 10−4~1.81 × 10−1, all of which is below the safety threshold of 1. The results of this study will provide scientific support for the fine pollution control and environmental management of industrial contaminated sites with BTEX as their typical pollutants.